Given differential equation is "(D-2D'+5)(D^2+D'+3)z = e^{3x}+4y sin(x-y)"
General solution z = Complement solution + Particular solution.
Auxiliary equation of given differential equation is
"(D-2D'+5)(D^2+D'+3)z = 0 \\\\\n\\implies (D-2D'+5)z = 0 \\hspace{0.05 in} and \\hspace{0.05 in} (D^2+D'+3)z = 0".
For "(D^2+D'+3)z = 0," assume "z = Ae^{hx+ky}" is solution,
so "Ae^{hx+ky}(h^2+k+3) =0 \\implies h^2+k+3 = 0."
So complement solution(C.S.) = "e^{-5x}\\phi (y+2x)+\\sum Ae^{hx+ky}" where "h^2+k+3=0".
Particular solution(P.S.) of given differential equation is
P.S. = "\\frac{1}{(D-2D'+5)(D^2+D'+3)} e^{3x}+4\\frac{1}{(D-2D'+5)(D^2+D'+3)}y sin(x-y) \\\\"
"= \\frac{1}{(3-2(0)+5)(3^2+0+3)} e^{3x}+ 4\\frac{1}{D^3-2D^2D'+DD'+5D^2-2D'^2+3D-D'+15}ysin(x-y) \\\\\n=\\frac{1}{96} e^{3x} + A(x,y)"
Comments
Leave a comment